Capital Expenditure and Environmental Disclosure: Profitability’s Role in Driving Financial Performance - Yohanna Thresia Nainggolan; Andhika Januardyh; Truly Wulandari; Ferica Christinawati Putri; Rizky Agusriyanti Irna (CV. Sakura Digital Nusantara, 2026)
Purpose – This study investigates financial performance determinants, focusing on capital expenditure (capex) and environmental management accounting practices in cost allocation and disclosure, with profitability acting as a mediating variable. Design/methodology/approach – A quantitative approach was applied using secondary data from 30 property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Data analysis employed the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to assess both direct and mediating relationships. Finding/Results – The results reveal that capex and environmental disclosure do not significantly affect financial performance. Moreover, profitability fails to mediate the relationship between capex, environmental disclosure, and financial performance. These findings highlight that investments in capital and environmental initiatives may require a longer-term horizon before influencing profitability and financial performance. Originality/Value – This research introduces a novel perspective by integrating capex and environmental disclosure into one analytical framework and testing profitability as a mediator in the Indonesian property sector context, which remains underexplored.